The Effect of the Herringbone Technique on Reading Comprehension - Rengganis Siwi Amumpuni (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
The purpose of this research is to know the effect of the Herringbone technique on students' reading comprehension. A quasi-experimental was used in this research and the sample was 20 students of Guidance and conselling department . Test was used in this research to collect the data and  the data was analyzed by paired sample T-test by using SPSS. The result of this research, there was a significant effect of the herringbone to the students 'reading comprehension. It can be seen from the value of the t-test that the score was  higher  than t- table (11.212 > 2.086).  Therefore, it can be stated that the there is a significant effect of Heringbone technique on students’ reading comprehension.